Letter from John L. Leboute to James Curtis Booth, July 30, 1879 - Leboute, John L. (1879)
John L. Leboute, Chief Clerk of the United States Mint Superintendent's Office, places an order for standard silver dollar ingots.
Keywords: Booth, James Curtis, 1810-1888; Silver ingots; United States Mint; Mint of the United States; Leboute, John L.